Genetics, paleontology, and macroevolution - Levinton, Jeffrey S. (Cambridge University Press, 2001)
This expanded and updated second edition offers a comprehensive look at macroevolution and its underpinnings, with a primary emphasis on animal evolution. From a Neodarwinian point of view, the book integrates evolutionary processes at all levels to explain the diversity of animal life. It examines a wide range of topics including genetics, speciation, development, evolution, constructional and functional aspects of form, fossil lineages, and systematics, and --in a major new chapter--takes a hard look at the Cambrian explosion. The author delves into the age of molecular science and integrates important recent contributions made to our understanding of evolution.